If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 7s + -4 Reorder the terms: 6 = -4 + 7s Solving 6 = -4 + 7s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-7s' to each side of the equation. 6 + -7s = -4 + 7s + -7s Combine like terms: 7s + -7s = 0 6 + -7s = -4 + 0 6 + -7s = -4 Add '-6' to each side of the equation. 6 + -6 + -7s = -4 + -6 Combine like terms: 6 + -6 = 0 0 + -7s = -4 + -6 -7s = -4 + -6 Combine like terms: -4 + -6 = -10 -7s = -10 Divide each side by '-7'. s = 1.428571429 Simplifying s = 1.428571429
| 2+2p=2-2p | | 1.82=Log(x) | | 2(-4)-3=x | | 5x+4=6x-42+8 | | 7+m=6 | | 2p+4p-7x+3=4p+5-3x | | -5x-6=-1 | | V^2-2v-5=-3v-3 | | 12x-8=15x-14 | | -5(x-3)=5(x-3) | | 5m+3n-2m-8n= | | (x+2)(7x+8)=0 | | 9-4+5h+3x= | | 9x/2=3x | | 9-4+53+32= | | 25c^2-121g^2=0 | | Y=3/4x-9;(-8,-18) | | 4y+10=-26 | | (14x+5)+(10x+15)=80 | | 6x+10=9x-11 | | 8n-3=15+2n | | 6y-9=45 | | 3/1*(8X/7-9/7) | | 3/1*(8X-9/7) | | 12x^3+6x^2-5x-3=0 | | 2m^2+9m+17=8 | | 3x+6-2=10 | | X+3+x+x-4x-4=6x-20 | | abs(2*x-5)=7 | | 5=S+4 | | -27+x=x+29 | | 3x+2y=3x-4 |